Typology of Tomato Cropping Systems and Determinants of Preharvest Losses in Western Cameroon - Roland Wilfried Titti; Anne Stéphanie Etoga; Pierre Germain Ntsoli; Georges Marius Kossi Etame; Asafor Henry Chotangui; Réné Mbonomo Bikomo; Aoudou Yaouba (Scientifica)
Preharvest losses, which are often neglected, limit the availability of fresh tomato fruit to varying degrees in tomato-based cropping systems in Cameroon. Increasing tomato yields requires identifying, understanding, and controlling the factors responsible for preharvest losses in the identified cropping systems. Field surveys were conducted in three production areas of western Cameroon (Foumbot, Bansoa, and Dschang) to characterize cropping systems and growers, quantify production losses, and identify causal factors associated with losses and proffer solutions. One hundred and ninety-six growers were interviewed in 13 villages, using purposive sampling to select zones and simple random sampling to select growers. Factor analysis for mixed data (FAMD) and canonical discriminant analysis, combined with multinomial logistic regression, were used to analyze the collected data. The FAMD results indicated that 72% of the farm variability was expressed through technical route, preharvest losses, and technical mastery. The tomato-based cropping systems were classified into three types: (1) a pure cultivation system that consumes excessive synthetic fertilizers and results in significant losses; (2) a pure cultivation system that consumes high amounts of synthetic fertilizers and moderate amounts of organic fertilizers with moderate losses; and (3) a cultivation system that involves moderate synthetic fertilizer consumption, extremely low organic amendment, and low losses. Preharvest losses can be significantly affected by the unregulated use of synthetic fertilizers. The study’s implications are many, affecting agricultural practices, policy, economic stability, and food security in Cameroon. A more sustainable and productive tomato industry can be achieved by addressing preharvest losses through informed strategies. To address this issue, it is crucial to establish fertilization protocols that consider the soil’s fertility status and the tomato’s essential macro- and micronutrient requirements.